Peran Kontrak Istishna dalam Mendorong Pertumbuhan Ekonomi Syariah TinjauanTeoritis dan Praktis - Andi Asti Yuninsi; A. Nur Husnul Khatimah; Sindi Ramadani; Akmal Aswad; Kamaruddin Kamaruddin (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The growth of the Islamic economy in Indonesia requires financing instruments that are not only in line with Islamic principles but also capable of driving the real sector productively. Istisna' contracts, which involve the sale of goods by order, offer a promising solution for financing construction projects, manufacturing, and micro-businesses. This study aims to explore the definition, role, and implementation of istisna' contracts in supporting the growth of the Islamic economy. Using a descriptive qualitative method based on literature review and normative-economic approaches, the study finds that istisna' contracts can enhance productivity, create employment opportunities, and support sustainable economic development. However, their implementation still faces challenges such as limited public understanding, financing risks, and a lack of education for business actors. Therefore, efforts to optimize the use of istisna' in Islamic financial institutions are essential